2009
DOI: 10.1029/2008gl036568
|View full text |Cite
|
Sign up to set email alerts
|

Role of ocean biology‐induced climate feedback in the modulation of El Niño‐Southern Oscillation

Abstract: [1] El Niño-Southern Oscillation (ENSO) properties can be modulated by many factors; most previous studies have focused on physical aspects of the climate system in the tropical Pacific. Ocean biology-induced feedback (OBF) onto physics and bio-climate coupling have been the subject of much recent interest, revealing striking model dependence and even conflicting results. Current satellite data are able to resolve the space-time structure of oceanic signals both in biology and physics, providing an opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 18 publications
0
55
0
Order By: Relevance
“…In response to increased chlorophyll concentrations, a reduction in ENSO amplitude is reported in one full GCM (Wetzel et al 2006), and in two intermediate coupled models with statistical atmospheres and simplified ecosystems (Timmermann and Jin 2002;R.-H. Zhang et al 2009); and an increase in amplitude is reported in two full GCMs (Lengaigne et al 2007;Anderson et al 2007), and in two intermediate coupled models with full ecosystems (Marzeion et al 2005;Ballabrera-Poy et al 2007). The implicit null hypothesis in the studies above is that light absorption through chlorophyll strengthens (or weakens) ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…In response to increased chlorophyll concentrations, a reduction in ENSO amplitude is reported in one full GCM (Wetzel et al 2006), and in two intermediate coupled models with statistical atmospheres and simplified ecosystems (Timmermann and Jin 2002;R.-H. Zhang et al 2009); and an increase in amplitude is reported in two full GCMs (Lengaigne et al 2007;Anderson et al 2007), and in two intermediate coupled models with full ecosystems (Marzeion et al 2005;Ballabrera-Poy et al 2007). The implicit null hypothesis in the studies above is that light absorption through chlorophyll strengthens (or weakens) ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…Many sensitivity studies have shown that adequately accounting for short-wave radiation penetration and its spacial and seasonal variation is important for simulating sea surface temperature (SST) and mixed layer depth at low latitude, equatorial undercurrents, and tropical cyclones and El Niño-Southern Oscillation (ENSO) (Schneider and Zhu, 1998;Nakamoto et al, 2001;Rochford et al, 2001;Murtugudde et al, 2002;Timmermann et al, 2002;Sweeney et al, 2005;Marzeion et al, 2005;Anderson et al, 2007;BallabreraPoy et al, 2007;Zhang et al, 2009;Jochum et al, 2010;Gnanadesikan et al, 2010;Liu et al, 2012). The solar radiation absorption is influenced by ocean colour on a global scale, so the bio-physical feedbacks have a global impact on the simulated results, including sea-ice thickness in the Arctic Ocean and the MOC (Lengaigne et al, 2009;Patara et al, 2012).…”
Section: Penetrative Short-wave Radiationmentioning
confidence: 99%
“…For example, studies using simplified coupled atmosphere-ocean models reported a reduction in ENSO magnitude in response to increased chlorophyll concentrations (Timmermann and Jin 2002;Zhang et al 2009). Specifically, Timmermann and Jin (2002) showed that changes in the shortwave absorption profile within the mixed layer intensify the asymmetry of ENSO, and suggested that the negative biological feedback may compensate for the systematic bias of sea surface temperatures (SSTs) in current climate models.…”
Section: Introductionmentioning
confidence: 99%